Students' Perspectives on Curricular Ultrasound Education at German Medical Schools - Recker, Florian; Barth, Gregor; Lo, Hendra; Haverkamp, Nicolas; Nürnberg, Dieter; Kravchenko, Dmitrij; Raupach, Tobias; Schäfer, Valentin Sebastian (Frontiers in Medicine, 2021)
Background Despite ultrasound being an inherent part of medical education, only a few German medical schools have established a comprehensive ultrasound curriculum. This study aimed to explore medical students’ perspectives on ultrasound in medical education (USMed). Results Between January 1st, 2019 und June 30th, 2019, an online survey was conducted among German medical students via the students’ associations and their respective teaching facilities. The survey consisted of 17 items regarding USMed. Statements were rated on a 4-point Likert scale for agreement. In total, 1040 students from 31 German medical faculties participated. The majority (1021, 98.2%) reported a very high to high interest in curricular USMed. Students agreed (n=945, 90.9%) that USMed would be helpful along their entire course of medical studies. Considering the best starting time for USMed, the opinions of German medical students diverged: students studying in a model curriculum preferred to start in the second year (40.7%) while 49% of the students studying in a traditional curriculum preferred to start in the third year (p= <0.001). An insufficient allotment of time for USMed in the planned curriculum (675, 65%) and a lack of coursesrun by medical faculty (305, 29.4%) were listed as perceived significant barriers to the participation in USMed. Peer teaching was regarded as an effective method in realizing USMed by 731 (70.3%) students. Conclusion German medical students are very interested and willing to participate in USMed. There appears to be a high demand for US courses offered by medical schools.